Comparison of Knowledge about Cellulite and Its Reduction Methods among Women and Men - Hołda, Katarzyna; Polak-Bielawska, Dagmara; Kutaj , Aleksandra; Savitskaya, Tatyana; Błaszczyk , Wiktoria; Wiczkowski, Dawid (Quality in Sport, 2025)
Introduction and purpose Cellulite (gynoid lipodystrophy, GLD) is a disorder of adipose tissue characterized by fibrotic degeneration of connective tissue and structural changes within the subcutaneous layer. It mainly affects women, regardless of age and body weight, while in men it occurs less frequently and is usually associated with hormonal disturbances. The pathogenesis of cellulite is complex and involves impaired microcirculation, adipocyte hypertrophy, increased vascular permeability, genetic predisposition, and an unhealthy lifestyle. The aim of this study was to assess the knowledge of women and men regarding cellulite and its reduction methods, as well as to analyze the relationship between the degree of severity and factors such as gender, age, BMI, and lifestyle. Materials and method The study included 104 participants; after verification, 99 respondents (69 women and 30 men) were qualified for the analysis. A diagnostic survey was conducted using an original questionnaire consisting of 22 closed and one open-ended question. The responses regarding the occurrence of cellulite, the level of knowledge, and the applied preventive methods were analyzed. Results Cellulite occurs more frequently and in more advanced stages in women than in men. The severity of changes correlates with higher Body Mass Index (BMI), poor diet, and low physical activity. Most respondents demonstrate general knowledge about cellulite but do not undertake professional treatments, which may result from limited awareness, high costs, or doubts about the effectiveness of procedures. Conclusions Gynoid lipodystrophy is a common aesthetic issue whose severity depends on lifestyle and physiological factors. Public knowledge about its prevention and therapy is moderate and should be improved through education and the promotion of healthy habits.